Brazilian Biodiversity Natural Products Database: BrNPDB - Neves, Fillipe A.; R. V. Carvalho, Alice; M. Campos, Lívia; L. N. de Oliveira, Thainan; Valli, Marilia; Pilon, Alan C.; Riechert, Thomas; Bolzani, Vanderlan S.; Marx, Edgard; J. Mócsy, István; R. V. do Carmo, Paulo; Schmidt-Dichte, Stefan (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
Released in 2013, the NuBBEDB is one of the best sources of natural products from Brazilian biodiversity. However, new possibilities have emerged with advances in scientific research and technologies. In this study, we demonstrate and discuss the development of the Brazilian Biodiversity Natural Products Database (BrNPDB), the relevance of Natural Products databases in Brazil, the materials and methods for data modeling, integration, standards and generated data from the cutting-edge sources, applications and technologies. The results show how BrNPDB upgrades NuBBEDB in many ways and contributes to the growing demand for platforms that enable more effective integration of chemical, biological, and ecological data.